Coverage of Vitamin A Supplementation among Under-Five Children in Hegarmanah Village, Jatinangor in August 2014 - Putri, Nadia Asmarani Hidayat; Istriati, Istriati; Djais, Julistio T.B. (Althea Medical Journal, 2017)
Background: The vitamin A supplementation program conducted every February and AugustÂ  aims to reduce children morbidity and mortality. Motherâs knowledge on the importance of vitamin A is crucial to succeeding this program. This study aimed to examine the coverage of the program among under-five children and the motherâs knowledge about vitamin A supplementation in Hegarmanah Village, Jatinangor in August 2014.Methods: This was a descriptive cross-sectional study involving mothers of children aged 6â59 months in eight RWs in Hegarmanah Village. The mothers were interviewed to find out whether their children received vitamin A supplementation. Additional questionnaire-based data about motherâs knowledge on vitamin A was also collected. The subjects in this study were the mothers of 220 under-five children. Data collection was obtained by direct interviews with the mothers during their visit to the Puskesmas or during home visits toÂ  children who missed the Posyandu appointments.Results: Two hundred and fourteen (97.27%) children received vitamin A supplementation and only 6 (2.73%) did not. The questionnaires revealed that 94 children (96%) received vitamin A, while 4 (4%) did not. The motherâs level of knowledge in vitamin A was either poor (1%), moderate (37%), or good (62%).Conclusions: The coverage of vitamin A supplementation in Hegarmanah Village reaches 97.27% and the motherâs understanding about vitamin A is generally good.Â DOI:Â 10.15850/amj.v4n2.1079